2022
DOI: 10.3390/jcm11133640
|View full text |Cite
|
Sign up to set email alerts
|

It Is All about Pressure

Abstract: Glaucoma is an ocular disease caused by elevated intraocular pressure that leads to progressive optic neuropathy. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The findings in the study have shown that there was neuroprotection from cell death in rat and mouse models of glaucoma that were fed with oral supplements of pyruvate [ 130 ]. Other clinical trials used nicotinamide and pyruvate in a phase II clinical trial and yielded significant momentary improvement in visual function, supporting the findings in the former experimental research and indicating a role for these agents in neuroprotection for individuals with glaucoma; this emphasizes the necessity for lasting studies to establish the longitudinal therapeutic effects of these nutrients [ 226 ], even if glaucoma has traditionally been exclusively all about pressure [ 227 ].…”
Section: Resultsmentioning
confidence: 63%
“…The findings in the study have shown that there was neuroprotection from cell death in rat and mouse models of glaucoma that were fed with oral supplements of pyruvate [ 130 ]. Other clinical trials used nicotinamide and pyruvate in a phase II clinical trial and yielded significant momentary improvement in visual function, supporting the findings in the former experimental research and indicating a role for these agents in neuroprotection for individuals with glaucoma; this emphasizes the necessity for lasting studies to establish the longitudinal therapeutic effects of these nutrients [ 226 ], even if glaucoma has traditionally been exclusively all about pressure [ 227 ].…”
Section: Resultsmentioning
confidence: 63%